Human Resources in Canada : Changing Attitudes and Roles - Haythorne, George (Relations industrielles / Industrial Relations, 1969)
The author observes how Canadians have influenced and have been influenced by their environment and thus tries to understand more fully how, through individual and collective action, their participation, development and enjoyment in today's world may be more fully achieved.